2002
DOI: 10.1007/s10209-002-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Web self-efficacy, age, and Web experience on bookmark manipulation

Abstract: This paper presents a study that examines the impact of age, Web experience, and Web self-efficacy across the adult life span on users' bookmark management behaviors. It was hypothesized that Web selfefficacy would mediate the effect of age and Web experience on bookmark manipulation. Six hundred users, sampled from the Project 2000 and 7th WWW User survey data, were used to examine this model. Using structural equation modeling techniques, it was found that the effect of age on bookmark manipulation was fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown the contributing effect of web self-efficacy on internet usage and satisfaction (Kurniawan et al, 2002;Roca et al, 2005). Against this background, this study hypothesizes that web self-efficacy will be significantly related to portal effectiveness dimension (i.e.…”
Section: Antecedents Of Portal Effectivenessmentioning
confidence: 86%
“…Numerous studies have shown the contributing effect of web self-efficacy on internet usage and satisfaction (Kurniawan et al, 2002;Roca et al, 2005). Against this background, this study hypothesizes that web self-efficacy will be significantly related to portal effectiveness dimension (i.e.…”
Section: Antecedents Of Portal Effectivenessmentioning
confidence: 86%
“…Regarding web portal usage, direct or indirect contributing effects of web self-efficacy on web portal usage were reported by a number of prior studies (i.e. Kurniawan, Ellis, & Allaire, 2002, Roca, Chiu, & Martinez, 2006. Atkinson and Kydd's (1997) study reported that undergraduate and graduate level students' ability to work with computer was strongly and positively associated with website use.…”
Section: Perceived Self-efficacy (Pse)mentioning
confidence: 97%
“…There are several previous studies related to the topic of a person's anxiety in various areas [24][25][26][27], such as in Yanto's research [28], who conducted a study on students' anxiety by applying computational models of variable precision rough sets and the BAI (Beck Anxiety Inventory). The author found that there were many types of anxiety according to the triggers and then classified students into specific categories based on the anxiety they had.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The BAI questionnaire assesses the level of respondents' anxiety using a scale based on the respondents' answers to the existing 20 questions. There are four scales in BAI, namely low (0-7), medium (8)(9)(10)(11)(12)(13)(14)(15), high (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and severe . In this experiment, the BAI questionnaire was filled out by respondents after reading the three news articles provided in the context of real news content, and this can provoke impulses and respondents' memories to trigger anxiety.…”
Section: Anxiety Measurementmentioning
confidence: 99%